(N‐Heterocyclic carbene)Pd(triethylamine)Cl2 as precatalyst for the synthesis of Poly(triarylamine)s. Issue 22 (18th September 2013) - Sprick, Reiner Sebastian; Hoyos, Mario; Chen, Ming‐Tsz; Turner, Michael Lewis; Navarro, Oscar
ABSTRACT The use of a highly active, air‐, and moisture‐stable N‐heterocyclic carbene‐palladium(II) complex for the polymerization of anilines and aryl dibromides or dichlorides by Buchwald‐Hartwig coupling is presented. In comparison to previous catalytic systems, higher molecular weight polymers with improved yields were obtained in shorter reaction times. The first examples of fabrication of OFETs with polytriarylamines synthesized with aryl dichlorides and anilines are also presented. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4904–4911